Functional genome analysis and anti-Helicobacter pylori activity of a novel bacteriocinogenic Lactococcus sp. NH2-7C from Thai fermented pork (Nham) - Engkarat Kingkaew; Weerapong Woraprayote; Auttaporn Booncharoen; Kanidta Niwasabutra; Thitiphorn Janyaphisan; Ratha-Korn Vilaichone; Yoshio Yamaoka; Wonnop Visessanguan; Somboon Tanasupawat (My University, 2023)
Helicobacter pylori, linked to gastric diseases, is targeted for probiotic treatment through bacteriocin production. Bacteriocins have gained recognition for their non-toxic effects on host cells and their ability to combat a wide range of pathogens. This study aimed to taxonomically characterize and evaluate the safety and probiotic properties of the novel species of Lactococcus sp. NH2-7C isolated from fermented pork, as well as its bacteriocin NH2-7C, both in vitro and in silico. Comparative genotypic analysis revealed an average nucleotide identity of 94.96%, an average amino acid identity of 94.29%, and a digital DNA-DNA hybridization value of 63.80% when compared to Lactococcus lactis subsp. lactis JCM 5805T. These findings suggest that strain NH2-7C represents a novel species within the genus Lactococcus. In silico assessments confirmed the non-pathogenic nature of strain NH2-7C and the absence of genes associated with virulence and biogenic amine formation. Whole-genome analysis revealed the presence of the nisA gene responsible for nisin A production, indicating its potential as a beneficial compound with anti-Helicobacter pylori activity and non-toxic characteristics. Probiotic assessments indicated bile salt hydrolase and cholesterol assimilation activities, along with the modulation of interleukin-6 and tumour necrosis factor-α secretion. Strain NH2-7C demonstrated gastrointestinal tolerance and the ability to adhere to Caco-2 cells, affirming its safety and probiotic potential. Additionally, its ability to produce bacteriocins supports its suitability as a functional probiotic strain with therapeutic potential. However, further in vitro and in vivo investigations are crucial to ensure its safety and explore potential applications for Lactococcus sp. NH2-7C as a probiotic agent.
Keywords: Lactococcus; Probiotics and Fermented Foods